Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Salon Natayu - Agus Susanti (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This study aims to determine the influence of price, product quality, and service quality on customer satisfaction at Salon Natayu. The approach used was quantitative, with data collection techniques through questionnaires distributed to Salon Natayu customers, with a total of 53 respondents (using census techniques). The data were analyzed using multiple linear regression analysis with the help of SPSS version 20. The results of the study show that the three independent variables (price, product quality, and service quality) simultaneously have a positive effect on customer satisfaction. However, partially, the price variable has the most dominant influence on customer satisfaction. The conclusion of this study shows that price is the most influential factor on customer satisfaction, followed by service quality, while product quality has the least influence. These findings indicate that a competitive pricing strategy is a crucial aspect for Salon Natayu in maintaining and improving customer satisfaction. In addition, continuous improvement of service quality is also necessary to create a better customer experience. This research is expected to be a reference for salon managers in formulating more effective marketing strategies as well as for future research that examines the factors that affect customer satisfaction in the beauty services industry.